France's position on the Polish-Bolshevik war 1919-1920 - Hussein , Dr. Zahraa Razaq (Thi Qar Arts Journal, 2023)
France emerged victorious from the First World War, but had to face complex international problems of regional, ideological and military nature. Its former ally, Tsarist Russia, which represented a counterweight to the defeated but powerful Germany, was in the midst of a civil war, in which the Bolsheviks prevailed and began to declare the necessity of exporting the revolution to Western European countries. As a result, the Red Army, which advanced westward, clashed with the newly established Polish state, which was completely dependent on the Western countries.For the Poles, this was a struggle with both communism and the perennial Russian imperialism. The Western countries helped Poland, especially France, which was seen as the real wall of Western Europe against the Bolsheviks and their communist ideology, and the assistance provided by the French army contributed to some extent to the victory of the Polish Republic, but the Paris government was contradictory regarding the disputed regional issues. To appreciate the nature of this French - Russian - Polish "triangle", it must be seen in a larger historical context in which the Poles were never an equal partner to the French. Received 6/6/2023,  Accepted 5/8/2023  , Published 30/9/2023.